Lower Cranial Nerve Schwannomas - Zanib Javed; Haseeb Waheed; Nasr Hussain; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2025)
Lower cranial nerve (LCN) schwannomas are rare, benign peripheral nerve sheath tumours arising from cranial nerves IX–XII. Though uncommon, they pose significant clinical challenges due to their complex anatomical location and potential for neurological deficits. Jugular foramen schwannomas (JFS) and hypoglossal schwannomas (HS) are the most prevalent subtypes. Clinical presentation varies by nerve involvement, ranging from hoarseness and dysphagia to tongue atrophy and paroxysmal cough. Diagnosis relies heavily on MRI and CT imaging, with differentiation from paragangliomas being critical. Classification systems guide surgical planning, with gross total resection (GTR) being the goal, though subtotal resection (STR) is preferred in cases with dense neural adherence to preserve function. Gamma knife radiosurgery (GKRS) offers an effective alternative for small or residual lesions. Treatment must balance tumor control with preservation of neurological function, requiring a multidisciplinary and individualized approach. Keywords: Schwannoma, Benign Neoplasms, Cranial nerve neoplasms